Dancing for the Snake: Possession, Gender, and Identity in the Worship of Manasā in Assam. (28th August 2018) - Urban, Hugh B
Abstract: This article examines the worship of the snake goddess Manasā in Assam, with special attention to the dynamics of gender, identity, and spirit possession. Specifically, the article focuses on two different forms of possession performance in honor of the goddess: the more ecstatic and bloody performance by male dancers at Kāmākhyā temple and the more folklorized and domesticated performance by female dancers on urban stages. Borrowing some ideas from Judith Butler, the article argues that both possession dances enact a kind of "subversion of identity." This includes not only a subversion of traditional gender identity, as male dancers are possessed by female deities and female dancers enact masculine roles; rather it also involves a profound subversion of the boundaries between the "Hindu" and the "tribal, " between the "Sanskritic" and the "vernacular, " and, ultimately, between the human and the divine.